Pendidikan olahraga hibrida dan pendekatan permainan langkah: Meningkatkan keterampilan bola voli - Karisman, Vicki Ahmad (Universitas Nusantara PGRI Kediri, 2023)
Mastering the technique of playing volleyball is important for every player. This will come in handy in gaming. Mastering it will make it easier to play and win. This study aims to determine whether step play and a hybrid approach to sport instruction will improve the skills of volleyball players. An experimental research methodology using a one-shot case study design was applied. This study was attended by 36 elementary school students using total sampling technique. They were instructed to participate in a joint sports education program between the Sport Education Model (SEM) and the Step Game Approach (SGA) for 14 meetings spread over two months, twice a week. The instruments used in this study were the Sport Orientation Questionnaire (SOQ) and the Game Performance Assessment Instrument (GPAI) were used to collect data. The results show good game performance, with yields exceeding 80% and a high proportion of each SOQ indicator, with an average of >80%. This shows that the combined learning model between SEM and SGA makes a positive contribution to students' volleyball playing techniques and skills. Through this combined learning it is hoped that students can learn techniques as well as their playing skills in real situations.